PENGGUNAAN SENJATA API BAGI ANGGOTA SATUAN POLISI PAMONG PRAJA DI KOTA TARAKAN - , EVA KARTIKA YULIANTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The use of firearm for the members of the Civil Service Police Unit in Tarakan City is an manifestation of the certainty implementation in Section 24 of Government Regulation Number 6 Year 2010 on the Civil Service Police Unit states that in order to facilitate the duty implementation in the field, the members of the Civil Service Police Unit can be facilitated with firearm, in which the types and the use requirements are recommended by State Police Forve of Republic Indonesia. It is also supported with Minister of Domestic Affair Number 26 Year 2010 on the Use of Firearm for the Members of the Civil Service Police Unit. On the basis, the researcher would like to find out its use implementation and the law enforcement for the violation of the use of firearm done by the members of the Civil Service Police Unit in Tarakan City. The firearm mentioned in the Government Regulation Number 6 Year 2010 and the Minister of Domestic Affair Number 26 Year 2010 are not a kind of firearm as used by State Police Forve of Republic Indonesia, but a firearm with the kind of new revolver pistol of gas and empty bullet, bludgeon, and electrical stick. It causes a negative paradigm from general society and government apparatus. The approach that will be used in this research is juridical empirical, the data obtained from the research result in field is correlated to theories of normative study to be represented, so that the descriptive qualitative description is obtained to get detail and relevant answers as the prevailing rules. The reality in the field indicates that there are violations on the use of bludgeon and electrical stick firearm done by the members of the Civil Service Police Unit in Tarakan City. The use violation of bludgeon and electrical stick firearm has not been taken an actions as the prevailing law both from personnel law (the Government Regulation Number 53 Year 2010 on Official Servant Discipline) or criminal law.